Restitution workshop report of the results of the HOLPA survey in Burkina Faso - Orounladji Boko, Michel; Kouakou, Patrice; Sib, Ollo; Sanogo, Souleymane; Ouedraogo, Adama; Vall, Eric (2024)
This workshop report shares the synthesis of the information produced by the agroecological performance assessment survey of dairy farms in the Bobo-Dioulasso dairy milkshed, using the HOLPA tool, and the discussion of the results with stakeholders. Specifically, this involved: Present and discuss the results of the study with the stakeholders who took part in it; Verify the consistency of the results obtained with the stakeholders; Establish with stakeholders a hierarchy of performance indicators by dimension (agronomic, environmental, social and economic); Draw lessons and identify ways forward to achieve the LIP vision in line with the principles of agroecology.